Unveiling macrophage dynamics and efferocytosis-related targets in diabetic kidney disease: insights from single-cell and bulk RNA-sequencing - Zhang, Binshan; Wu, Yunqi; Wang, Zhongli; Gao, Suhua; Liu, Hongyan; Lin, Yao; Yu, Pei (Frontiers in Immunology, 2025)
BackgroundChronic inflammation and immune imbalance mediated by macrophages are considered pivotal in diabetic kidney disease (DKD). The study aims to clarify the macrophage heterogeneity and phenotype dynamics, and pinpoint critical targets within efferocytosis in DKD.MethodsUtilizing early human DKD sequencing data, we computed the potential communication between leukocytes and renal intrinsic cells. Subsequently, we scrutinized the single-cell RNA sequencing (scRNA-seq) data from CD45-enriched immune cells, concentrating on the macrophage subsets in DKD. Pseudotime trajectory analysis was conducted to explore cell development. Differential expression genes (DEGs) from macrophage subgroups and bulk RNA-sequencing were used to identify shared hub genes. The NephroseqV5 platform was employed to evaluate the clinical significance, and the expression of key molecules was validated in DKD tissues.ResultsMacrophage infiltration rose in DKD, causing inflammation through the release of chemokines. As time progressed, the number of resident macrophages substantially dropped, with diminishing M1-like and increasing M2-like phenotypes relative to early stages. Further analysis pointed to the most enrichment of macrophage function is the phagosome. We overlapped the DEGs with efferocytosis-related genes and identified key genes, including CD36, ITGAM, and CX3CR1, which exhibited significant correlations with macrophages and T cells. The Nephroseq database revealed that they are associated with proteinuria and renal function. Consistent with the validation set, in vivo experiments verified elevated expression levels of key molecules.ConclusionsIn essence, our research elucidated the dynamics in macrophage subtype transitions. It emphasized three pivotal genes as critical modulators of macrophage efferocytosis in DKD, indicating their potential as innovative biomarkers and therapeutic targets.